Small signal oscillatory instability control of power system using posicast controller and evolutionary programming - Mirfendereski, Shojaeddin (2014)
Oscillatory stability is a subcategory of Small Signal Stability (SSS) which is defined as the ability of power system to maintain synchronous operation under small disturbances. The oscillations usually are concerned with frequencies between 0.2 to 3 hertz. Modal analysis is being used for analysis of SSS. Different methods have been presented by the researchers for controlling SSS such as: using power system stabilizer, HVDC, FACT devices, etc. what is not considered in different methods is that how the stabilizer or a controller should present their output to the system, regarding to the dominant mode? The posicast controller aim is to mitigate the oscillations of lightly damped system. In this study for each oscillation mode that is concerned with oscillatory instability, a posicast is designed, tuned and placed at the output of the power system stabilizer (PSS). In this case the electrical torque which is produced by PSS will go through the posicast first which will give the signal a manner in a way that it does not excite the dominant mode in advance while keeping its effectiveness for the system. Also a compensator is needed to reduce the steady state disturbances of the posicast. The gain of this compensator is very important because, by optimizing it the performance of the posicast controller is improved. Two methods of optimization which are Evolutionary Programming (EP) and Genetic Algorithm (GA) were used to find the best value of the K and their comparative study were analyzed. Initially, to demonstrate the effect of the posicast controller the IEEE 9-bus test system was used. Then, the overall effects of the posicast controller and the optimization methods (EP and GA) were implemented on two different test systems i.e. The IEEE 39-bus test system and the 16-machine, 68-bus, 5-area test system. For each case, first of all, the whole system is analyzed. Then, for the most sensitive modes the posicast is tuned and designed. A system consists of eigenvalue, posicast and compensator is then designed and used as a fitness function of the EP and the GA to find the maximum acceptable value of the gain. In all three cases the posicast controller shows its positive effect to the total response of the system in case of disturbances. The comparison between them shows that both of them reach to results which are almost the same. However, the choice between these two depends on the expectations and the hardware limitations.